211k views
1 vote
Which expression is equivalent? (3−2x−2y−2)−3

A) 729x6y6
B) 1 729x6y6
C) 729 x6y6
D) x6y6 729

User AnV
by
5.9k points

2 Answers

6 votes


\text{Use:}\\\\(ab)^n=a^nb^n\\\\(a^n)^m=a^(nm)\\\\(3^(-2)x^(-2)y^(-2))^(-3)=(3^(-2))^(-3)(x^(-2))^(-3)(y^(-2))^(-3)\\\\=3^((-2)(-3))x^((-2)(-3))y^((-2)(-3))=3^6x^6y^6\\\\=\boxed{729x^6y^6\to C)}

User Tbarbe
by
5.7k points
2 votes

Answer:


729x^6y^6

Explanation:


(3^(-2)x^(-2)y^(-2))^(-3) =


3^(-2* (-3))x^(-2* (-3))y^(-2* (-3)) =


= 3^6x^6y^6


= 729x^6y^6

User Manuel Ferreria
by
5.8k points